Facile direct insertion of nitrosonium ion (NO+) into a ruthenium-aryl bond - Pat, Pak-Kei (2015)
An insertion reaction of nitrosonium ion (NO+) into the metal−carbon bond of cyclometalated ruthenium(II) complexes is prepared with experimental evidence supporting a bimolecular direct NO+ insertion into the metal−carbon bond (i.e., M−R + NO+ → [M−N(═O)−R]+) but not an intramolecular migratory insertion (i.e., R−M−(NO) + L → L−M−N(═O)R) as the reaction mechanism. Theoretical calculations suggest that the direct NO+ insertion into the M−C bond may be rationalized as a frontier orbital interaction between the [Ru−aryl]-dominated HOMO of the Ru(II) complexes and the LUMO of the NO+.